Socialization of Introduction and Benefits of Toefl Functions for Students SMA Swasta Pematangsiantar - Saragih, Sanju Febrio; Damanik, Olivia; Hutapea, Dewi Kristina; Silalahi, Ignastius; Herman, Herman; Grace, Ernest (Jurnal Pengabdian Nusantara, 2025)
This socialization activity on the introduction and benefits of the TOEFL function was conducted with the aim of enhancing the understanding of the students of SMA Swasta Teladan Pematangsiantar, particularly the eleventh-grade students, regarding the importance of the TOEFL test as one of the requirements in education and employment. TOEFL (Test of English as a Foreign Language) is an international standardized test that measures English language proficiency in four main skills: reading, listening, writing, and speaking. Unfortunately, many high school students still lack understanding about the function, format, and benefits of this test. Therefore, this socialization activity was designed to provide a comprehensive introduction to the concept of TOEFL, its test types (ITP, iBT, and CBT), question structure, and basic strategies for taking the test. Through material presentation, interactive discussions, and practice sessions, this activity is expected to motivate students to take English learning more seriously and to prepare themselves early. The results showed that students responded positively, with enthusiasm, and began to realize the importance of TOEFL as a valuable asset for their academic and professional future.